A152 D-LACTIC ACIDOSIS IN CHILDREN WITH SHORT BOWEL SYNDROME-A LITERATURE REVIEW AND REPORT OF TWO CASES. (15th March 2019) - AL HARTHY, F M; Zachos, M; Ratcliffe, E; Pai, N
Abstract: Background: D-lactic acidosis (D-LA) is an uncommon complication in children with Short Bowel Syndrome (SBS). The clinical presentation is characterized by episodes of neurological manifestations and severe metabolic acidosis. Diagnosis of D-LA is made by a combination of clinical assessment and biochemical measurement of D-lactic acid. Aims: This review of two cases aims to describe our recent experience in the management of DLA, and to review recent literature on the management of D-LA in patients with SBS. Methods: A literature search was performed using PubMed, and Google Scholar databases using the terms, "D-lactic acidosis", "short bowel syndrome", and "lactic acidosis in short bowel syndrome". Results: Case 1: A 4 year old male with SBS secondary to midgut volvulus at 5 months of age (27 cm of proximal jejunum, 3 cm of terminal ileum with intact ileocecal valve remaining) presented in July, 2018 with acute ataxia, slurred speech and altered mental status. Laboratory tests revealed a high anion gap metabolic acidosis with D-lactate level 8.89 mmol/L. The patient improved with fluid resuscitation, bicarbonate administration and cessation of oral feeds. He was discharged on oral Metronidazole for 14 days and bicarbonate 3/4 teaspoon three times a day. Case 2: A 12 year old male presented to the Emergency Department with episodes of frequent diarrhea, lethargy, dizziness and behavioral changes. He had a relevant past medical history of SBS secondary to congenital gastroschisis with jejunal and colonic atresia, and subsequent right hemicolectomy secondary to midgut volvulus. Investigations revealed metabolic acidosis with a D-lactate level of 4.26 mmol/L. He was managed with intravenous fluid, bicarbonate therapy and discharged on cycling antibiotics (Metronidazole) with rapid resolution of symptoms and normalization of acidosis and D-lactate levels. He presented again in August 2018 with recurrent neurological symptoms and D-lactate 7.48 mmol/L. His recurrent symptoms were felt to be likely due to small intestinal bacterial overgrowth (SIBO), given his elevated D-lactate levels and response to antibiotic therapy. Conclusions: D-lactic acidosis is a rare but serious complication of short bowel syndrome (SBS). Investigations for SIBO and empiric treatment with long-term, cycling antibiotics may be considered in patients who have repeated episodes of D-LA. Intestinal microbiota composition in children with SBS is an important factor influencing the clinical outcome. Further studies will be required to verify the incidence of D-LA in settings with chronic antibiotic use, and assessing the role of probiotics or fecal microbiota transplant in its management. Funding Agencies: None